Applications of Nanotechnology in Advanced Cosmeceuticals - Patil Khushi Sanjay; Akash S Jain; Divakar R Patil; Azam Z Shaikh; Sammeer R Saikh; S P Pawar (Recent Trends in Cosmetics, 2025)
Nanotechnology is the study and manipulation of atoms and molecules on the nanoscale, which is approximately 80,000 times smaller than the width of a human hair. By 2015, the global market for products incorporating nanomaterials is projected to reach $2.6 trillion. This field showcases significant progress in research and development by improving product performance and introducing innovative solutions.The usage of cosmetics has increased significantly throughout time, and they are thought to be the personal care product category with the quickest rate of growth. There are still concerns about the potential risks that nanoparticles may have to human health, which may go unnoticed due to their low toxicity, despite the rapid advancement of nanotechnology. Cutting-edge nanocarriers like Nanotechnology uses in cosmeceuticals P. S. G. V. P. M. COP. Shahada liposomes, niosomes, microemulsions, nanoemulsions, solid lipid nanoparticles, nanostructured lipid carriers, and nanospheres have revolutionized drug delivery, replacing conventional methods with more efficient and effective alternatives.Nanoparticles have improved features such as color, transparency, solubility, and other attributes, which is why nanotechnology has become so prevalent in the cosmetic sectors. Better known as UV filters, they offer superior UV absorption, which is why sunscreen formulations employ them widely over the globe without leaving an unwanted white film on users' skin. This page addresses the many applications, advantages, and kinds of nanomaterials as well as the potential and challenges of nanotechnology and how it applies to the cosmetics sector. Examining the pros and cons of nanotechnology.
Keywords: Cosmeceutical; Health risks; Nanometals; nanomaterials; nanotechnology